An improved turbulence model for predicting unsteady cavitating flows in centrifugal pump. Issue 5 (1st June 2015) - Wang, Jian; Wang, Yong; Liu, Houlin; Huang, Haoqin; Jiang, Linglin
Abstract : Purpose: – The purpose of this paper is to study the unsteady caivitating flows in centrifugal pump, especially for improving the turbulence model to obtain highly resolution results-capable of predicting the cavitation inception, shedding off and collapse procedures. Design/methodology/approach: – Both numerical simulations and experimental visualizations were performed in the present paper. An improved RCD turbulence models was proposed by considering three corrected methods: the rotating corrected method, the compressible corrected method and the turbulent viscosity corrected method. Unsteady RANS computations were conducted to compare with the experiments. Findings: – The comparison of pump cavitation performance showed that the RCD turbulence model obtained better performance both in non-cavitation and cavitation conditions. The visualization of the cavitation evolution was recorded to validate the unsteady simulations. Good agreement was noticed between calculations and visualizations. It is indicated the RCD model can successfully capture the bubbles detachment and collapse at the rear of the cavity region, since it effectively reduces the eddy viscosity in the multiphase region of liquid and vapor. Furthermore, the eddy viscosity, the instantaneous pressure and density distribution were investigated. The effectiveness of the compressibility was found. Meanwhile, the influence of the rotating corrected method on prediction was explored. It is found that the RCD model solved more unsteady flow characteristics. Originality/value: – The current work presented a turbulence model which was much more suitable for predicting the cavitating flow in centrifugal pump.